COMMUNITY-CENTERED REPRODUCTIVE HEALTH EDUCATION FOR MOTHERS IN RURAL KENYA (Proceedings of the International Conference on Public Health, 2023)
In Kilifi County, a coastal region of Kenya, one in five teenage girls begins childbearing. This represents the highest teen pregnancy rate in Kenya. Since 2016, Mtree, a non-profit organization registered in both the U.S. and Kenya, has conducted a multi-year field assessment in Maya village in rural Kilifi. The objective of this assessment was to identify the reproductive health needs of mothers through an explorative study to design a community-centered curriculum that would address the gaps identified from the needs assessment. In partnership with Pwani University, Mtree performed home visits and focused group interviews on interviews on a convenient sample of 69 women from 2016 to 2020. The village elders introduced interviewers and translators to the community and arranged group interviews. Each year the questionnaire varied as the subsequent questionnaire was based on previous findings. Since 2018, the questionnaire for mothers focused on their expectations for teen girls in the community, especially on teen pregnancy and job opportunities. Findings revealed that the primary challenges for Maya women were lack of job opportunities, inability to afford sanitary towels, lack of knowledge around and misunderstanding of reproductive health, and lack of male partner involvement. Mothers reported that the core factors that lead to unwanted early pregnancy included lack of reproductive health knowledge, sexual abuse, peer pressure, and poverty. The mother's primary values and concerns with reproductive health were assessed and integrated into the mother's family planning and teen pregnancy prevention program. In 2021, eight mothers of teen girls in grades 4 and 5 at Maya Primary School were recruited by village leaders and participated in the program and learn about how to communicate with teen girls on the topic of reproductive health, dating, and roles of women in the community and society.
Keywords: Teen pregnancy; Reproductive health education; Maternal health; Family planning